2018
DOI: 10.1016/j.lungcan.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the VeriStrat test in first line patients with non-small cell lung cancer treated with platinum-based chemotherapy

Abstract: VeriStrat provides valuable clinical information that may be used to support patient-physician conversations regarding prognosis and treatment options, and to identify a subset of patients who might benefit from other treatment strategies, possibly in the framework of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The BR.21 trial enrolled placebo-treated patients in second or higher line (VS-G median OS, 6.6 mo; VS-P median OS, 3.1 mo; HR, 0.44; 95% CI, 0.31-0.63; p < .001) [4]. In retrospective analyses of multiple cohorts, Ver-iStrat is prognostic for OS and progression-free survival (PFS) in patients treated with front-line platinum-based chemotherapy [5]. The prognostic and predictive capabilities have been replicated in prospective analyses, in patients treated with front-line platinum and pemetrexed (VS-G median PFS, 6.5 mo; VS-P median PFS, 1.6 mo; HR, 0.36; p < .001) [6], and VeriStrat has been shown to be predictive of differential therapeutic benefit between second-line chemotherapy and erlotinib [7].…”
Section: Introductionmentioning
confidence: 99%
“…The BR.21 trial enrolled placebo-treated patients in second or higher line (VS-G median OS, 6.6 mo; VS-P median OS, 3.1 mo; HR, 0.44; 95% CI, 0.31-0.63; p < .001) [4]. In retrospective analyses of multiple cohorts, Ver-iStrat is prognostic for OS and progression-free survival (PFS) in patients treated with front-line platinum-based chemotherapy [5]. The prognostic and predictive capabilities have been replicated in prospective analyses, in patients treated with front-line platinum and pemetrexed (VS-G median PFS, 6.5 mo; VS-P median PFS, 1.6 mo; HR, 0.36; p < .001) [6], and VeriStrat has been shown to be predictive of differential therapeutic benefit between second-line chemotherapy and erlotinib [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients classi ed as VS-G had signi cantly longer PFS and OS than VS-P patients. These results demonstrated that VS is a strong predictive test in NSCLC patients treated with platinum-based regimens in the rst line [10]. However, so far there has been no study using this VS method for the prediction of rst-line pemetrexed plus platinum-based chemotherapy or combined with bevacizumab for Chinese advanced lung adenocarcinoma patients.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that VS was a valid method to predict the e cacy of chemotherapy or targeted therapy for advanced NSCLC patients [7][8][9][10][11]. However, so far there has been no study using VS method for the prediction of rst-line pemetrexed based chemotherapy plus for Chinese advanced lung adenocarcinoma patients without EGFR sensitizing mutations, ALK or ROS1 rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…The VeriStrat test, originally developed for prediction of benefit from EGFR-TKIs in NSCLC, has been validated in numerous independent studies, demonstrating strong predictive [48,53] and prognostic [54][55][56] properties in various settings. For the purpose of this review we summarize the results of the application of the VeriStrat test to samples from advanced NSCLC patients treated with nivolumab in second and higher lines in the Lung cancer validation set [50], and with various immune checkpoint inhibitors in the scope of the INSIGHT registry study (NCT03289780) [49].…”
Section: The Veristrat Testmentioning
confidence: 99%